2010
DOI: 10.1590/s1413-81232010000600023
|View full text |Cite
|
Sign up to set email alerts
|

Informações sobre a morbidade hospitalar em idosos nas internações do Sistema Único de Saúde do Brasil

Abstract: Informações sobre a morbidade hospitalar em idosos nas internações do Sistema Único de Saúde do BrasilInformation on seniors' morbidity upon internments on the Brazilian Unified Health System

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
40

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 10 publications
2
20
0
40
Order By: Relevance
“…The association between the various comorbidities evaluated and polypharmacy found in this study is consistent with other studies of the elderly 17,32 . A study conducted in Japan found that polypharmacy was more common in the treatment of hypertension, hyperlipidemia, gastric ulcers and diabetes 33 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association between the various comorbidities evaluated and polypharmacy found in this study is consistent with other studies of the elderly 17,32 . A study conducted in Japan found that polypharmacy was more common in the treatment of hypertension, hyperlipidemia, gastric ulcers and diabetes 33 .…”
Section: Discussionsupporting
confidence: 92%
“…These diseases are the main causes of mortality among the global elderly population 33,34 . The high prevalence of diseases of the digestive system can often lead to the unnecessary intake of other drugs, thus explaining the use of polypharmacy in this population 32 . This condition can lead to a cascade of negative effects on the health of the elderly and on the health system.…”
Section: Discussionmentioning
confidence: 99%
“…These specialties manage various common diseases of aging such as pneumonia, chronic obstructive pulmonary disease (COPD), cardiovascular diseases such as heart failure (HF) and cerebrovascular accidents or strokes (CVA), in addition to fractures. 2,12,13 These situations often feature OIT as a therapeutic resource, used as needed by the patient. 4,18,20 In terms of evolution, approximately 15% of the elderly persons hospitalized and treated with OIT were discharged for treatment at home, which indicates the need for monitoring and longterm care, not only of the patient but also the the environment in which he or she lives, the household conditions and the care to which the patient has access.…”
Section: Discussionmentioning
confidence: 99%
“…1 The most frequent causes of hospitalization among the elderly in Brazil, among both genders, are heart and coronary disease and lung disease, which alternate as the most and second most common causes. 2 Hospitalization rates among those aged 80 or above are three times higher than among individuals aged between 55 and 59 years. 3 During hospitalization, administration of oxygen is one of the most important treatment methods for patients with hypoxia, which results from several common conditions such as cardiovascular events, chronic respiratory diseases and lower respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…Reconhecidamente, o envelhecimento populacional está relacionado com o aumento da prevalência de doenças crônicas não transmissí-veis, entre elas as cardiovasculares, pulmonares obstrutivas crônicas, do aparelho locomotor, endócrinas nutricionais e metabólicas, neoplasias e diabetes 8,9,10,11,12,13,14,15,16 . Esse quadro gera maior demanda nas internações hospitalares, tratamentos medicamentosos e na reabilitação dos pacientes, o que induz ao aumento dos gastos nas atenções secundária e terciária do Sistema Único de Saúde (SUS) 17 .…”
unclassified